UPAYA PENINGKATAN PRESTASI BELAJAR SISWA MATA PELAJARAN EKONOMI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS (TWO STAY TWO STRAY) PADA SISWA KELAS X A SMA PGRI 1 MAOSPATI MAGETAN TAHUN PELAJARAN 2012/2013 - Sudarmiani Sudarmiani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
Based on initial observations  and interviews  with high school Economics teacher  PGRI  1 Maospati  Magetan  note that the average  value of the cognitive  aspects of students  in the class XA is 62. These results  indicate  that the numbers  are still low com- pared  to other  classes.  The learning  process  is commonly  carried  out using  a model  of discourse  as a whole,  namely  the delivery  of content  to students  and interspersed   ques- tions and answers.  This leads to learning  as students  tend to be passive  and less meaning- fullearning   for students.  Students  gain experience  less direct,  and less teacher  provides opportunities   as well as self- confidence  in the students  to be active  in learning.  It  also adversely  affects  the affective  aspects  of students.   Based on these problems  researchers to  make  improvements   by  implementing   cooperative   learning  model  of two  stay  two stray  ( TSTS  ). The  learning  model  involves  students  actively  in learning  activities. Pakok mind model of cooperative  learning  are two stay two stray provide  an opportunity for groups  to share  results  and information  to other  groups.  The approach  used  in this study  is a qualitative  approach  to classroom  action  research  that  consists  of 2 cycles. Research  subject  is class XA SMA PGRI  1 Maospati  Magetan  , the number  of 32 stu- dents.  Data  collection  methods  used  in this  study  is a test  of the cognitive  aspects  of economic  subjects  in the form of daily tests at the end of the cycle, and affective  aspects of the observation  sheets during the learning  process.  The results  of observations  of stu- dents'  learning  in classroom  situations  XA SMA PGRI  1 Maospati  Magetan  increased, namely:   ( 1 ) The interest  and attention  of students  in the learning process  from 67.25% to 84.60%  increased   17.35%  ( 2 ) The active  participation   of students  in asking  from 54.10%  to  68.25%  an increase  of  14.15%  ( 3 ) the active  participation   of students  in answering  / expression  from 52.22%  to 69.45%  increased   17.23% ( 4 ) the level of stu- dent  discipline  in the process  of learning  from  60.500/0 to 78.13%  17.63%  an increase. The results  of observations  III group  activities  has increased,   namely:   ( 1 ) The active participation   of students  in an opinion  from  51.58%  to 68.75%  increased   17.17%  (2) The active participation   of students  in asking from 50.60% to 66.68%  increased  16.08% (3)the active participation   of students  in answering  questions  from 53.12%  to 71.88% increased18.76% (4)   Respect  tile opinion  of friends from 55.50%  to 74.850/0 increased 19,35%  (5)   Cooperation  in completing  a task group from 60.35% to 78.25%  17.90% an increase. Another thing shown by the increased learning outcomes from 65.63 % to 84.38%. Thus there is an increase  of 18.75% .While the average  value of learning  outcomes  in the first cycle is 71 increased  to 82 in the second cycle. Learning  model  two stay two stray ( TSTS ) can improve  cognitive  and affective  aspects  of students  by providing  a learning environment  that is fun discussions,  opportunities  for students to learn actively  exchange information  with peers and materials,   conveying  the idea to friends,  submit answers and questions  discussion  of the problem,  and it requires  cooperation  within  the group.